The addition of a quaternary group in biopolymeric material increases the adsorptive capacity of Acid Blue 25 textile dye - Mendes, Carolina Rosai [UNESP]; Dilarri, Guilherme [UNESP]; Stradioto, Marcia Regina [UNESP]; de Faria, Adriano Uemura [UNESP]; Bidoia, Ederio Dino [UNESP]; Montagnolli, Renato Nallin [UNESP] (Springer Nature, 2019)
The quaternization of chitosan molecules creates materials with high adsorptive capacity towards textile dyes, which renders them capable of rapidly removing such dyes from a solution. In this study, a novel material was synthesized in bead form to adsorb the Acid Blue 25 textile dye. The adsorption isotherms, kinetics, and thermodynamics of this new material were investigated. The beads were further characterized by FT-IR and SEM studies, as well as their rheological behavior. Bioassays with Daphnia similis analyzed the toxicity of the dye before and after treatments. The Freundlich isotherm model fitted to all the adsorption data in a pH range from 2.50 to 8.50. Kinetic studies showed that adsorption was ruled by an intraparticle diffusion process and reached equilibrium in 270 min, as 39.527 μg mg−1 of dye was sorbed to the beads. Thermodynamic studies showed that adsorption was a spontaneous and endothermic process. Thermodynamics also confirmed that the adsorption was proportionally influenced by higher temperatures. The FT-IR spectroscopy identified the adsorbate/adsorbent binding sites, thus confirming the occurrence of chemisorption. Post-treatment bioassays found a significant decrease in toxicity, obtaining just 10% of D. similis mortality after adsorption treatments. Therefore, the synthesized beads from this research can potentially be applied to the treatment of textile effluents.
Keywords: Chemisorption; Chitosan; Daphnia similis; Quaternary ammonia substituent group; Textile effluents; Toxicity test